Reflective Pedagogy as Humanistic Learning - Fathoni, Baharuddin (HISTORIKA, 2020)
AbstractThis Study aimed to elaborate further on education based on the paradigm of reflective pedagogy to realize intelligent and humanist learners. The Reflective Pedagogy Paradigm is a mindset in developing students' personalities into human beings. The Reflective Pedagogy Paradigm is an approach or learning model that applies reflection in finding values and learning by emphasizing students' experiences. The approach involves students' interaction with the material they learn with the teacher as a facilitator. The learning process is designed students as the center of the learning process and facilitates them to explore knowledge and values with full responsibility. Through this learning activity, students are expected to develop their ability to think and act (competence) and conscience, and they will be compassionate towards others. The process is successful if the students themselves find knowledge, understanding, skills, and values, and the task of educators is as a facilitator.